Disentangling the impacts of soil moisture and vapour pressure deficit on biodiversity patterns and conservation value of tropical forests in Ghana, West Africa - Forzia Ibrahim; Stephen Adu-Bredu; Arne Buechling; Akwasi Duah-Gyamfi; Shalom Addo-Danso; Yadvinder Malhi; Somidh Saha; Stephen Awuni; Emmanuel Tetteh Jumpah; Martin Svátek; Radim Matula (Biological Conservation, 2025)

Shrub aboveground biomass estimation considering bulk volume geometry: general and specific models for 14 species in the Mediterranean central Chile - Erico Kutchartt; Jorge Gayoso; Javier Guerra; Francesco Pirotti; Daniele Castagneri; Radim Matula; Yasna Rojas; Mark E. Olson; Martin Zwanzig (New Forests, 2025)

Past disturbances shape present tree size distribution in European temperate primary beech-dominated forests - Ruffy M. Rodrigo; Joseph L. Pettit; Pavel Janda; Jakob Pavlin; Dheeraj Ralhan; Daniel Kozak; Radim Matula; William Marchand; Radek Bače; Martin Dušátko; Tomás Kníř; Michal Frankovič; et al. (Forest Ecology and Management, 2024)

Drought resistance of major tree species in the Czech Republic - Yumei Jiang; William Marchand; Miloš Rydval; Radim Matula; Pavel Janda; Krešimir Begović; Dominik Thom; Alexandre Fruleux; Arne Buechling; Jakob Pavlin; Juliana Nogueira; Martin Dušátko; et al. (Agricultural and Forest Meteorology, 2024)

Structural changes caused by selective logging undermine the thermal buffering capacity of tropical forests - Erone Ghizoni Santos; Martin Svátek; Matheus Henrique Nunes; Juha Aalto; Rebecca A. Senior; Radim Matula; Roman Plichta; Eduardo Eiji Maeda (Agricultural and Forest Meteorology, 2024)

Shifts in intra-annual growth dynamics drive a decline in productivity of temperate trees in Central European forest under warmer climate - Radim Matula; Soňa Knířová; Jan Vítámvás; Martin Šrámek; Tomáš Kníř; Iva Ulbrichová; Miroslav Svoboda; Roman Plichta (Science of The Total Environment, 2023)

Multi-stemming enhances tree survival and growth in Borneo’s logged forests - Jakub Kvasnica; Radim Matula; Martin Rejžek; Robert M. Ewers; Terhi Riutta; Edgar C. Turner; Reuben Nilus; Martin Svátek (Forest Ecology and Management, 2023)

Natural Disturbances are Essential Determinants of Tree-Related Microhabitat Availability in Temperate Forests - Veronika Zemlerová; Daniel Kozák; Martin Mikoláš; Marek Svitok; Radek Bače; Marie Smyčková; Arne Buechling; Maxence Martin; Laurent Larrieu; Yoan Paillet; Catalin-Constantin Roibu; Ion Catalin Petritan; et al. (Ecosystems, 2023)
Assessing the impacts of natural disturbance on the functioning of complex forest systems are imperative in the context of global change. The unprecedented rate of contemporary species extirpations, coupled with widely held expectations that future disturbance intensity will increase with warming, highlights a need to better understand how natural processes structure habitat availability in forest ecosystems. Standardised typologies of tree-related microhabitats (TreMs) have been developed to facilitate assessments of resource availability for multiple taxa. However, natural disturbance effects on TreM diversity have never been assessed. We amassed a comprehensive dataset of TreM occurrences and a concomitant 300-year disturbance history reconstruction that spanned large environmental gradients in temperate primary forests. We used nonlinear analyses to quantify relations between past disturbance parameters and contemporary patterns of TreM occurrence. Our results reveal that natural forest dynamics, characterised by fluctuating disturbance intervals and variable severity levels, maintained structurally complex landscapes rich in TreMs. Different microhabitat types developed over time in response to divergent disturbance histories. The relative abundance of alternate TreMs was maximised by unique interactions between past disturbance severity and elapsed time. Despite an unequal distribution of individual TreMs, total microhabitat diversity was maintained at constant levels, suggesting that spatially heterogeneous disturbances maintained a shifting mosaic of habitat types over the region as a whole. Our findings underscore the fundamental role of natural processes in promoting conditions that maximise biodiversity potential. Strict conservation and management systems that preserve natural disturbance outcomes, including associated biological legacies, may therefore safeguard biodiversity at large scales.

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

ForestClim —Bioclimatic variables for microclimate temperatures of European forests - Stef Haesen; Jonas J. Lembrechts; Pieter De Frenne; Jonathan Lenoir; Juha Aalto; Michael B. Ashcroft; Martin Kopecký; Miska Luoto; Ilya Maclean; Ivan Nijs; Pekka Niittynen; Johan van den Hoogen; et al. (Global Change Biology, 2023)
Microclimate research gained renewed interest over the last decade and its importance for many ecological processes is increasingly being recognized. Consequently, the call for high‐resolution microclimatic temperature grids across broad spatial extents is becoming more pressing to improve ecological models. Here, we provide a new set of open‐access bioclimatic variables for microclimate temperatures of European forests at 25 × 25 m 2 resolution.

Networking the forest infrastructure towards near real-time monitoring – A white paper - Roman Zweifel; Christoforos Pappas; Richard L. Peters; Flurin Babst; Daniel Balanzategui; David Basler; Ana Bastos; Mirela Beloiu; Nina Buchmann; Arun K. Bose; Sabine Braun; Alexander Damm; et al. (Science of The Total Environment, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

ForestTemp – Sub‐canopy microclimate temperatures of European forests - Stef Haesen; Jonas J. Lembrechts; Pieter De Frenne; Jonathan Lenoir; Juha Aalto; Michael B. Ashcroft; Martin Kopecký; Miska Luoto; Ilya Maclean; Ivan Nijs; Pekka Niittynen; Johan van den Hoogen; et al. (Global Change Biology, 2021)
Ecological research heavily relies on coarse‐gridded climate data based on standardized temperature measurements recorded at 2 m height in open landscapes. However, many organisms experience environmental conditions that differ substantially from those captured by these macroclimatic (i.e. free air) temperature grids. In forests, the tree canopy functions as a thermal insulator and buffers sub‐canopy microclimatic conditions, thereby affecting biological and ecological processes. To improve the assessment of climatic conditions and climate‐change‐related impacts on forest‐floor biodiversity and functioning, high‐resolution temperature grids reflecting forest microclimates are thus urgently needed. Combining more than 1200 time series of in situ near‐surface forest temperature with topographical, biological and macroclimatic variables in a machine learning model, we predicted the mean monthly offset between sub‐canopy temperature at 15 cm above the surface and free‐air temperature over the period 2000–2020 at a spatial resolution of 25 m across Europe. This offset was used to evaluate the difference between microclimate and macroclimate across space and seasons and finally enabled us to calculate mean annual and monthly temperatures for European forest understories. We found that sub‐canopy air temperatures differ substantially from free‐air temperatures, being on average 2.1°C (standard deviation ± 1.6°C) lower in summer and 2.0°C higher (±0.7°C) in winter across Europe. Additionally, our high‐resolution maps expose considerable microclimatic variation within landscapes, not captured by the gridded macroclimatic products. The provided forest sub‐canopy temperature maps will enable future research to model below‐canopy biological processes and patterns, as well as species distributions more accurately.

Historical Disturbances Determine Current Taxonomic, Functional and Phylogenetic Diversity of Saproxylic Beetle Communities in Temperate Primary Forests - Daniel Kozák; Marek Svitok; Michal Wiezik; Martin Mikoláš; Simon Thorn; Arne Buechling; Jeňýk Hofmeister; Radim Matula; Volodymyr Trotsiuk; Radek Bače; Krešimir Begovič; Vojtěch Čada; et al. (Ecosystems, 2021)

Effective determination of biomass in oak coppices - Martin Šrámek; Marie Matoušková; Klára Lengálová; Michaela Kruttová; Tzvetan Zlatanov; Luboš Úradníček; Lenka Ehrenbergerová; Radim Matula (Trees, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Do the rich get richer? Varying effects of tree species identity and diversity on the richness of understory taxa - Juliette Chamagne; C. E. Timothy Paine; Donald R. Schoolmaster; Robert Stejskal; Daniel Volarřík; Jan Šebesta; Filip Trnka; Tomáš Koutecký; Petr Švarc; Martin Svátek; Andy Hector; Radim Matula (Ecology, 2016)
Understory herbs and soil invertebrates play key roles in soil formation and nutrient cycling in forests. Studies suggest that diversity in the canopy and in the understory are positively associated, but these studies often confound the effects of tree species diversity with those of tree species identity and abiotic conditions. We combined extensive field sampling with structural equation modeling to evaluate the simultaneous effects of tree diversity on the species diversity of understory herbs, beetles, and earthworms. The diversity of earthworms and saproxylic beetles was directly and positively associated with tree diversity, presumably because species of both these taxa specialize on certain species of trees. Tree identity also strongly affected diversity in the understory, especially for herbs, likely as a result of interspecific differences in canopy light transmittance or litter decomposition rates. Our results suggest that changes in forest management will disproportionately affect certain understory taxa. For instance, changes in canopy diversity will affect the diversity of earthworms and saproxylic beetles more than changes in tree species composition, whereas the converse would be expected for understory herbs and detritivorous beetles. We conclude that the effects of tree diversity on understory taxa can vary from positive to negative and may affect biogeochemical cycling in temperate forests. Thus, maintaining high diversity in temperate forests can promote the diversity of multiple taxa in the understory.

The sprouting ability of the main tree species in Central European coppices: implications for coppice restoration - Radim Matula; Martin Svátek; Jana Kůrová; Luboš Úradníček; Jan Kadavý; Michal Kneifl (European Journal of Forest Research, 2012)